Kajian Implementasi Balance Scorecard untuk Mengukur Indikator Kinerja Dinas Pemadam Kebakaran Pemda DKI Jakarta - Dr. Solihin, Ak.,M.Si.,CA , Dr. Solihin, Ak.,M.Si.,CA; Karsam, Karsam (LPPM Swadaya Institute of Business and Communication, 2024)
The purpose of this research is to discuss the public services which in any prevention and mitigation efforts by creating a system of fire prevention and control productively. As we know Firehouse has both prevention and curative functions as to anticipate and conduct preventive efforts to avoid fire to happen and to reduce risk or to minimize fires, it should be conducted effective and efficiently. Research method used literature study and performance measurement balance scorecard method and cost benefit analysis. The conclusion is that the firehouse as the government agency given the mandate should prevent and handle a fire in such a way that reduce the risk to a minimu